1974
DOI: 10.1039/c39740000973
|View full text |Cite
|
Sign up to set email alerts
|

Phenylphosphoranyl radicals: are they tetrahedral or trigonal bipyramidal?

Abstract: The e.s.r. spectra of phenylphosphoranyl radicals [Ph,PX,-,Y]-show that, depending on the nature of X and Y, these radicals fall into two types in which the unpaired electron is centred mainly on phosphorus or on the aromatic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…However, hydrogen sulphide proved to be a good co-solvent for Ph,P and permitted the spectrum of [ButOPPh,] *, which has a ligand-x electronic structure, * to be observed a t lower temperatures than before. 19 a(lH), 7.9, a ( 2 H ) 4.4 G, g 2.0031, as expected if the unpaired electron is located on one ring rather than delocalised over all three (see Figure 3). A t higher temperatures lineshape effects indicated that electron exchange between the rings was taking place on the e.s.r.…”
Section: X I V Lsupporting
confidence: 67%
“…However, hydrogen sulphide proved to be a good co-solvent for Ph,P and permitted the spectrum of [ButOPPh,] *, which has a ligand-x electronic structure, * to be observed a t lower temperatures than before. 19 a(lH), 7.9, a ( 2 H ) 4.4 G, g 2.0031, as expected if the unpaired electron is located on one ring rather than delocalised over all three (see Figure 3). A t higher temperatures lineshape effects indicated that electron exchange between the rings was taking place on the e.s.r.…”
Section: X I V Lsupporting
confidence: 67%
“…Alkoxytriphenylphosphoranyl radicals show strong absorption bands in the visible region of the spectrum (Xmax 430 nm, emax ~6200 M-1 cm-1 for 1) which extend well into the near-IR region; these characteristics probably reflect an extensive delocalization of the unpaired electron on the aromatic rings and are consistent with the low values of the 3IP hyperfine coupling constants. 5 Our results for triphenylborane provide conclusive evidence for the stepwise nature of the reaction with Zezv-butoxy radicals. In fact, the behavior of triphenylborane parallels that of phosphorus compounds, though it is clear that the tetracoordinate boranyl radical intermediate is considerably less stable than its phosphorus counterpart.…”
Section: Discussionsupporting
confidence: 54%
“…An analogous case of a nearly complete transfer of spin density away from a heteroatom occurs in the phosphorus-centered radical cPPh(OEt) 2 (OBu-t), where the spin density is delocalized onto the aromatic ring. 13 The hyperfine coupling of germanium in 3a, a( 73 Ge) ¼ 15.0, is much smaller than that in the stable pyramidal radical [(Me 3 Si) 2 N] 3 Gec (171.0 G), 14 and in fact even smaller than reported for the planar radical (t-Bu 2 MeSi) 3 Gec (20.0 G). 15 The relatively low 73 Ge hyperfine coupling constant in radical 3a is consistent with delocalization of the unpaired electron away from the Ge atom.…”
Section: Resultsmentioning
confidence: 87%
“…2c: 1 H NMR (benzene, DMSO-d 6 capillary): d 5.71 (2H, s), 4.52 (4H, m, J H-P ¼ 6.3 Hz, J H-H ¼ 6.2 Hz), 1.41 (18H, s), 1.19 (24H, dd, J H-P ¼ 2.0 Hz, J H-H ¼ 6.2 Hz); 29 Si NMR: d À71.2 (t, J Si-P ¼ 1.3 Hz); 31 P NMR: d 126.2; 13 C NMR: d 110.4, 65.5 (d, J C-P ¼ 11.1 Hz), 51. 3, 30.6, 24.5. 5b: 1 H NMR (benzene, DMSO-d 6 capillary): d 4.94 (4H, m, J H-H ¼ 6.0 Hz), 2.94 (8H, s), 1.39 (36H, s), 1.33 (24H, d, J H-H ¼ 6.0 Hz); 29 Si NMR: d 67.9 (d, J Si-P 16.4 Hz); 31 P NMR: d 129.7; 13 C NMR: 65.0 (d, J C-P ¼ 10.9 Hz), 51. 2, 44.1, 30.8, 24.8. 5c: 1 H NMR (benzene, DMSO-d 6 capillary): d 4.55 (4H, m, J H-P ¼ 6.0 Hz, J H-H ¼ 6.3 Hz), 2.90 (4H, s), 1.66 (18H, s), 1.22 (24H, dd, J H-P ¼ 5.2 Hz, J H-H ¼ 6.3 Hz); 29 Si NMR: d À69.1 (t, J Si-P ¼ 3.2 Hz); 31 P NMR: d 126.0; 13 C NMR: d 65.2 (d, J C-P ¼ 10.8 Hz), 50.9, 41.5, 29.3, 25.0.…”
Section: Nmr Spectroscopymentioning
confidence: 99%